2018
DOI: 10.1093/police/pay046
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Herman Goldstein Problem-Oriented Policing Awards from 1993-2017

Abstract: This article analysed the finalists and winners of the Herman Goldstein Problem-Oriented Policing projects from 1993 to 2017, which provides a sample of 153 cases. The article reflects on the changes in the problem-solving process overtime in regards to the nature of crime and quality of life problems addressed, the involvement of collaborative partners, the use of technology, and the level of sophistication of the assessment phase of the Scanning, Analysis, Response, and Assessment model. The processes used b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Engaging in these activities, presumably, is critical for engaging in an iterative problem-solving process. In addition, and possibly as a result of superficial analysis and response generation, officers pursuing POP strategies may still rely more on standard law enforcement responses than on those designed to produce lasting change (Schnobrich-Davis, Block, and Lupacchino, 2018). More research and morerigorous research are still needed to understand which POP responses are most effective, particularly for reducing violent crimes committed with guns.…”
Section: Problem-solving Approachesmentioning
confidence: 99%
“…Engaging in these activities, presumably, is critical for engaging in an iterative problem-solving process. In addition, and possibly as a result of superficial analysis and response generation, officers pursuing POP strategies may still rely more on standard law enforcement responses than on those designed to produce lasting change (Schnobrich-Davis, Block, and Lupacchino, 2018). More research and morerigorous research are still needed to understand which POP responses are most effective, particularly for reducing violent crimes committed with guns.…”
Section: Problem-solving Approachesmentioning
confidence: 99%
“…Editor's note: A recent review of the Goldstein submissions from 1993 to 2017 (Schnobrich-Davis et al 2018) concluded that there has been 'significant progress in the development of problem-solving and its continuation as a practice within police agencies' (page 12), with increased use of partners in helping to deliver appropriate responses to crime and public safety problems.…”
mentioning
confidence: 99%